2016
DOI: 10.1055/s-0042-107254
|View full text |Cite
|
Sign up to set email alerts
|

Immunmodulatory and Antiproliferative Properties of Rhodiola Species

Abstract: The traditional medicines of Asia and Europe have long used various Rhodiola species, which are endemic to the subarctic areas of the northern hemisphere, as tonic, adaptogen, antidepressant, and anti-inflammatory drugs. In order to establish the therapeutic uses of these plants in modern medicine, the pharmacological effects of Rhodiola sp. have been widely studied. Indeed, the most amply researched species, Rhodiola rosea, has been shown to possess antioxidant, adaptogenic, antistress, antimicrobial, immunom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 55 publications
0
37
0
1
Order By: Relevance
“…Furthermore, the survey findings indicated that the adaptogen /vitamin preparation reduced stress perceptions to a greater extent than the corresponding placebo (Table 5). Elevated HS-CRP is strongly associated with an increased incidence of heart attack, stroke, type 2 diabetes and metabolic syndrome [2,12,[16][17][18][19], and the combination product used in this study significantly reduced these levels.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, the survey findings indicated that the adaptogen /vitamin preparation reduced stress perceptions to a greater extent than the corresponding placebo (Table 5). Elevated HS-CRP is strongly associated with an increased incidence of heart attack, stroke, type 2 diabetes and metabolic syndrome [2,12,[16][17][18][19], and the combination product used in this study significantly reduced these levels.…”
Section: Discussionmentioning
confidence: 64%
“…A rapidly growing body of research literature supports the concept that inflammation plays a pivotal role in cardiovascular and metabolic diseases [2,12,[16][17][18]25]. The anti-inflammatory and stress protective effects of adaptogens are believed to be associated with the homeostatic regulation of several different pathways and mechanisms including the hypothalamic-pituitaryadrenal axis, the neuro-endocrine-immune complex, and key stress response mediators [11,23,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salidroside, one of the most potent compounds isolated from the plant Rhodiola rosea, has been suggested to possess anti-inflammatory, anti-proliferative, and anti-oxidant activities in various animal model systems and cell cultures [7, 8]. This compound has recently attracted considerable attention because of accumulating data demonstrating its strong inhibitory effect on bladder carcinoma, colorectal cancer [9], and breast cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-oxidative, immunomodulatory, anti-tumor and anti-microbial activity have been shown so far [2, 3]. Mechanism of action of various Rhodiola species depends on quality and quantity of the biological active compounds.…”
Section: Introductionmentioning
confidence: 99%